A177 INADEQUATE OR EXCESSIVE GESTATIONAL WEIGHT GAIN IN INFLAMMATORY BOWEL DISEASE AND IMPACT ON PREGNANCY AND NEONATAL OUTCOMES. (21st February 2022) - Nguyen, D M; Tandon, P; Govardhanam, V; Hanna, Y; Tao, J J; Cepo, J; Maxwell, C; Huang, V
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at a risk of adverse pregnancy outcomes. Prior studies have suggested that inadequate gestational weight gain is associated with preterm birth and intrauterine growth restriction. Aims: We sought to characterize the proportion of people with IBD who gain inadequate or excessive weight during pregnancy and how this affects pregnancy and neonatal outcomes. Methods: Pregnant patients with ulcerative colitis (UC), Crohn's disease (CD), and inflammatory bowel disease unclassified (IBD-U) were identified retrospectively at Mount Sinai Hospital from 2016 to 2020. Total gestational weight gain (GWG) was calculated as the difference of the weight recorded at time of labor and pre-pregnancy weight. GWG was categorized as inadequate GWG, adequate GWG, and excessive GWG based on the pre-pregnancy body-mass index and standards set by the U.S. Institute of Medicine. Neonatal-related outcomes were also recorded for each patient and included preterm delivery, small for gestational age (SGA) and large for gestational age (LGA). Multiple logistic regression was used to assess the association between gestational weight gain and outcomes while controlling for maternal age, history of gestational diabetes, and preconception disease activity. Results: 225 pregnancies were included (106 UC, 115 CD, 4 IBD-U). Forty-eight patients (21.3%) had inadequate, 91 (40.4%) adequate, and 86 (38.2%) excessive GWG. People of East Asian, African, and Hispanic ethnicity were more likely to have inadequate GWG. People with inadequate GWG were more likely than those with excessive GWG to have lower preconception BMI (21.7 vs 25.5 kg/m 2, P=0.001). IBD type was not associated with inadequate GWG or excessive GWG, though people with inadequate GWG were 2-fold less likely to be on anti-TNF therapy. People with excessive GWG were more likely than those with adequate GWG to have babies with higher birth weight (3, 364g vs 3, 132g, P=0.003). People with inadequate GWG were not at increased risk of SGA compared to those with adequate GWG (adjusted odds ratio (aOR), 1.01; 95% CI: 0.37 – 2.71, P=0.99). Those with excessive GWG were substantially less likely to have an infant with SGA (aOR, 0.23; 95% CI: 0.07 – 0.72, P=0.01). On multivariable logistic regression analysis, excessive GWG was not associated with increased odds of delivering infants with LGA (aOR, 1.46; 95% CI: 0.54 – 3.95, P=0.46). There was no association between non-adequate gestational weight gain and preterm delivery or Caesarean delivery. Conclusions: Less than half of persons with IBD have adequate GWG during pregnancy. Inadequate GWG was not associated with poor neonatal outcomes, and excessive GWG appeared to protect against delivering infants born SGA. Funding Agencies: None